2001
DOI: 10.1105/tpc.13.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Single-Celled Cotton Fiber Elongation by Developmentally Reversible Gating of Plasmodesmata and Coordinated Expression of Sucrose and K+ Transporters and Expansin

Abstract: Each cotton fiber is a single cell that elongates to 2.5 to 3.0 cm from the seed coat epidermis within ‫ف‬ 16 days after anthesis (DAA). To elucidate the mechanisms controlling this rapid elongation, we studied the gating of fiber plasmodesmata and the expression of the cell wall-loosening gene expansin and plasma membrane transporters for sucrose and K ؉ , the major osmotic solutes imported into fibers. Confocal imaging of the membrane-impermeant fluorescent solute carboxyfluorescein (CF) revealed that the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
307
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 240 publications
(318 citation statements)
references
References 39 publications
11
307
0
Order By: Relevance
“…2,14 Potassium and sucrose are imported from the underlying seed coat cells, either symplasmically through the plasmodesmata (PD) or apoplasmically across cell wall space and plasma membrane by their respective transporters, energized by the plasma membrane and tonoplast H + -ATPases, respectively. 4,5 GhKT1, encodes a cotton K + transporter, is weakly expressed in fibers at 6 DAA when the PD are open. However, its mRNA abundance increases significantly at 10 DAA when the PD are closed and then rapidly decreases to undetectable level at 16 DAA when the PD are re-opened (Fig.…”
Section: Multiple Players In Controlling Of Cell Turgor During Fiber mentioning
confidence: 99%
See 4 more Smart Citations
“…2,14 Potassium and sucrose are imported from the underlying seed coat cells, either symplasmically through the plasmodesmata (PD) or apoplasmically across cell wall space and plasma membrane by their respective transporters, energized by the plasma membrane and tonoplast H + -ATPases, respectively. 4,5 GhKT1, encodes a cotton K + transporter, is weakly expressed in fibers at 6 DAA when the PD are open. However, its mRNA abundance increases significantly at 10 DAA when the PD are closed and then rapidly decreases to undetectable level at 16 DAA when the PD are re-opened (Fig.…”
Section: Multiple Players In Controlling Of Cell Turgor During Fiber mentioning
confidence: 99%
“…6 Cytological studies, along with transcriptional investigations, revealed that after a slow start, the elongation rate of cotton fiber increases at ~2-3 DAA followed with a log phase during the first ten days. 1,7 The elongation reaches the maximal rate at ~10-15 DAA 5 and rapidly declines at ~16 DAA onwards when fibers switch to intensive secondary cell wall cellulose biosynthesis. 5,8 The rate and duration of fiber elongation establish the final length attained, which is a key factor determining fiber quality and yield.…”
mentioning
confidence: 99%
See 3 more Smart Citations